ENRICHMENT OF GENETIC RESOURCES OF VEGETABLE CROPS WITH NON-TRADITIONAL VEGETABLE CROPS - Buriev Khasan Chutbaevich; Okkuziev Ilkhom Oktamovich; Sobitov Obidjon Sahibboevich; Tugelova Zeynep Besequlovna (Journals Park Publishing, 2022)
The article presents information about the current state of the collection of vegetable and fruit crops stored in the gene pool and the practice of enriching this gene pool with non-traditional vegetable crops.
Keywords: gene pool, crop samples, collection, genetic resources, population.